Nodavirus RNA Replication Protein A Induces Membrane Association of Genomic RNA - Van Wynsberghe, Priscilla M. (American Society for Microbiology, 2007)
Positive-strand RNA virus genome replication occurs in membrane-associated RNA replication complexes, whose assembly remains poorly understood. Here we show that prior to RNA replication, the multifunctional, transmembrane RNA replication protein A of the nodavirus flock house virus (FHV) recruits FHV genomic RNA1 to a membrane-associated state in both Drosophila melanogaster and Saccharomyces cerevisiae cells. Protein A has mitochondrial membrane-targeting, self-interaction, RNA-dependent RNA polymerase (RdRp), and RNA capping domains. In the absence of RdRp activity due to an active site mutation (A(D692E)), protein A stimulated RNA1 accumulation by increasing RNA1 stability. Protein A(D692E) stimulated RNA1 accumulation in wild-type cells and in xrn1(−) yeast defective in decapped RNA decay, showing that increased RNA1 stability was not due to protein A-mediated RNA1 recapping. Increased RNA1 stability was closely linked with protein A-induced membrane association of the stabilized RNA and was highly selective for RNA1. Substantial N- and C-proximal regions of protein A were dispensable for these activities. However, increased RNA1 accumulation was eliminated by deleting protein A amino acids (aa) 1 to 370 but was restored completely by adding back the transmembrane domain (aa 1 to 35) and partially by adding back peripheral membrane association sequences in aa 36 to 370. Moreover, although RNA polymerase activity was not required, even small deletions in or around the RdRp domain abolished increased RNA1 accumulation. These and other results show that prior to negative-strand RNA synthesis, multiple domains of mitochondrially targeted protein A cooperate to selectively recruit FHV genomic RNA to membranes where RNA replication complexes form.